Խեթական KUB XXVI 62 սեպագիր տեքստը և Վերին Եփրատի ավազանի պատմական աշխարհագրության խնդիրները - Քոսյան, Արամ («Զանգակ - 97»)
The article deals with the Hillile text KUB XXVI 62 (late XV Century B.C.), which conlains the lisl of cities, from where soldiers were recruited for the Hittite army. Some of these cities should bc located on the territory of later Armenian province of the Upper Armenia, particularly in the River Gayl basin. Among these cities Litta probably is idenlical with the medieval Armenian city of Litaric, about 24 Roman miles (= km) to the east of Nikopolis (near modern Shapin-Karahisar) on the route towards Satala.
Keywords: Հայոց պատմություն; Սեպագրություն